2021
DOI: 10.3389/fsurg.2021.736680
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Cage Subsidence in Anterior Cervical Decompression and Fusion: Zero Profile Anchored Spacer (ROI-C) vs. Conventional Cage and Plate Construct

Abstract: Background: Anterior cervical discectomy and fusion (ACDF) has been widely performed to treat cervical generative diseases. Cage subsidence is a complication after ACDF. Although it is known that segmental kyphosis, acceleration of adjacent segmental disease, and restenosis may occur due to cages subsidence; however detailed research comparing zero-profile cages (ROI-C) and conventional plate and cage construct (CPC) on cage subsidence has been lacking.Objective: The objectives of this study was to compare the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 31 publications
0
15
1
Order By: Relevance
“…The incidence of subsidence in the PEEK group is within the published range of 14.9-66% [10,[20][21][22][23]; in contrast, the Al 2 O 3 group showed incidence of subsidence below this range.…”
Section: Discussionmentioning
confidence: 57%
“…The incidence of subsidence in the PEEK group is within the published range of 14.9-66% [10,[20][21][22][23]; in contrast, the Al 2 O 3 group showed incidence of subsidence below this range.…”
Section: Discussionmentioning
confidence: 57%
“…In conclusion, we believe that this result was within our expectation, considering that the anterior titanium plates of the ACDF group would provide additional structural reinforcement. Comparing the four-year clinical follow-up of Jin et al ’s28 result, the mean disc height loss in their two groups after surgery was around 1.8 mm, and the cage subsidence rate was higher in the SA group (66.67%) than in the conventional plate group (38.46%). In this retrospective study, we observed that the loss of disk height was higher in the SA cage group than in the CPC group (0.35±0.27 vs. 0.11±0.34 mm) at the five-year follow-up compared with one month postoperation.…”
Section: Discussionmentioning
confidence: 90%
“…Similarly, Pinder et al 19 also demonstrated increased subsidence in ACDF without reliable instrumentation. Meanwhile, Jin et al 20 further investigated the effect of zero-profile cages and conventional cage-plate combination on postoperative subsidence and showed increased subsidence by the former, demonstrating the incidence of subsidence to be associated with instrument's rigidity. Therefore, it seemed plausible to conclude that both instrument's presence and strength played an important role in the initiation of subsidence.…”
Section: Discussionmentioning
confidence: 99%
“…also demonstrated increased subsidence in ACDF without reliable instrumentation. Meanwhile, Jin et al 20 . further investigated the effect of zero‐profile cages and conventional cage‐plate combination on postoperative subsidence and showed increased subsidence by the former, demonstrating the incidence of subsidence to be associated with instrument's rigidity.…”
Section: Discussionmentioning
confidence: 99%